Reasons for Adoption and Non-adoption of Direct Seeded Rice in Punjab - Kamalpreet Kaur and Prabhjot Kaur, (Indian Journal of Extension Education, 2017)
Direct seeded rice (DSR) technique is becoming popular nowadays because of its low-input demanding nature. There aremany reasons which motivated the respondents for adoption of direct seeded rice such as water saving, labour saving andprofitable technique etc. All the respondents started direct seeded rice because it gives better results than transplantingmethod. To study the reasons of adoption and non-adoption of DSR, the study was conducted in five districts of Punjab;Moga, Mukatsar Sahib, Faridkot, Sangrur and Patiala. From each district one village and from each village 15 farmers ofDSR and 15 of transplanting were selected by using random sampling technique. Data were collected by using personalinterview method. The data reveal that 98.67 per cent of the respondents started DSR as it saves time spent on paddynursery and reduce the transplanting cost. Whereas 97.33 per cent desired to save water and reducing labour cost, easypractice which did not need puddling exercise and 96 per cent of the respondents showed their interest in DSR and adoptedthe DSR technique. For the non-adoption of DSR, 90.67 per cent of the respondents reported that there was high risk tocrop in DSR. Whereas 89.33 per cent reasoned non-adoption due to non-availability of DSR drill and 88 per cent forgermination failure of direct seeded crop and due to more requirement of weedicide.